MOTIVASI DAN PERSEPSI WISATAWAN TENTANG DAYA TARIK DESTINASI TERHADAP MINAT KUNJUNGAN KEMBALI DI KOTA WISATA BATU - Sayangbatti, Dilla Pratiyudha; Baiquni, Muhammad (JURNAL NASIONAL PARIWISATA, 2013)
This research was conducted in order to find the motivation and tourist perceptions of the attractiveness of tourist destinations of interest in a return visit in the City of Rock. Formulation of the problem in this study were: 1). what is the motivation that encourages tourists to travel in Batu; 2). How does the perception of tourists to the attractiveness of tourist destinations Batu; 3). How does motivation and perception Pull the power rating of the tourist destinations of interest in a return visit in Batu.The method used is random sampling. Used also accidental sampling technique. Respondents in this study was the visitors who come in Batu as a tourist attraction sites. Sample size using the formula of the total population is not known. The results of the analysis of the highest tourist motivation is wanting to enjoy the beauty of nature and the search for a new experience. Tourist perceptions of tourist destination Batu declared facilities, saranaprasarana and authenticity is very adequate, but need to improve in the field of transport is considered tourists still lacking. This study also showed that tourists who have visited the City Tour Stone wanted to do a return visit. This requires managers to municipalities and ODTW to improve the existing infrastructure and maintaining the original natural tourist attraction